PERBANDINGAN KINERJA KEUANGAN PADA PT. GARUDA INDONESIA TBK. DAN PT. AIR ASIA INDONESIA TBK. TAHUN 2017– 2022 - Ika Dwi Lestari; Trisnia Widuri; Kukuh Harianto (Cahaya Ilmu Bangsa, 2024)
Abstrack Nowadays, the air transportation industry in the country is facing relatively rapid development. This development has led to stronger competition among airline companies, even seen by the increase in total air travel routes in Indonesia. Financial ratio analysis is a useful method for evaluating a company's financial performance through utilizing information from financial statements and comparing it to all kinds of approaches to explain the condition of a company's financial performance. This study aims to determine the comparison of the financial performance of PT Garuda Indonesia Tbk. and PT Air Asia Indonesia Tbk. Year 2017-2022. The sample in this study is the financial statements of PT Garuda Indonesia Tbk and PT Air Asia Indonesia Tbk for the period 2017-2022. The population in this study were PT Garuda Indonesia Tbk and PT Air Asia Indonesia Tbk. This study uses SPSS 25 as a statistical test tool to test the normality test, Independent Sample t-test, and Mann-Whitney-U test. The results showed that based on the current ratio and quick ratio liquidity ratios, there were insignificant differences. Solvency ratios debt to asset ratio and debt to equity ratio there are differences that are not significant. Activity ratios total asset turn over and inventory turn over there are insignificant differences. Profitability ratios net profit margin and return on assets there are insignificant differences. Keyword : Current Ratio, Quick Ratio, Debt To Asset Ratio ,Debt To Equity Ratio, Total Asset Turn Over, Inventory Turn Over, Net Profit Margin, Return On Aset Abstrak Pada masa kini, industri transportasi udara di tanah air menghadapi perkembangan yang relatif pesat. Perkembangan tersebut menyebabkan persaingan yang semakin kuat sesama perusahaan penerbangan, bahkan terlihat oleh peningkatan total jalur perjalanan udara di Indonesia. Analisis rasio keuangan ialah metode yang bermanfaat guna mengevaluasi performa keuangan perusahaan melalui memanfaatkan informasi dari laporan keuangan dan membandingkannya pada segala macam pendekatan menjelaskan kondisi kinerja keuangan suatu perusahaan. Penelitian ini bertujuan untuk mengetahui perbandingan kinerja keuangan PT. Garuda Indonesia Tbk. dan PT. Air Asia Indonesia Tbk. Tahun 2017-2022. Sampel pada penelitian ini adalah laporan keuangan PT Garuda Indonesia Tbk dan PT Air Asia Indonesia Tbk periode 2017-2022. Populasi pada penelitian ini adalah PT Garuda Indonesia Tbk dan PT Air Asia Indonesia Tbk. Penelitian ini menggunakan SPSS 25 sebagai alat uji statistik untuk menguji uji normalitas, uji Independent Sample t-test, dan uji Mann-Whitney-U. Hasil penelitian menunjukkan berdasarkan rasio likuiditas current ratio dan quick ratio terdapat perbedaan yang tidak signifikan. Rasio solvabilitas debt to asset ratio dan debt to equity ratio terdapat perbedaan yang tidak signifikan. Rasio aktivitas total asset turn over dan inventory turn over terdapat perbedaan yang tidak signifikan. Rasio profitabilitas net profit margin dan return on asset terdapat perbedaan yang tidak signifikan. Kata Kunci : Current Ratio, Quick Ratio, Debt To Asset Ratio ,Debt To Equity Ratio, Total Asset Turn Over, Inventory Turn Over, Net Profit Margin, Return On Aset